Prevalence and risk of violence and the mental, physical and sexual health problems associated with human trafficking: an updated systematic review. (12th April 2016) - Ottisova, L.; Hemmings, S.; Howard, L.M.; Zimmerman, C.; Oram, S.
Abstract : Background: To update and expand on a 2012 systematic review of the prevalence and risk of violence and the prevalence and risk of physical, mental and sexual health problems among trafficked people. Method: Systematic review and meta-analysis. Searches of 15 electronic databases of peer-reviewed articles and doctoral theses were supplemented by reference screening, citation tracking of included articles and expert recommendations. Studies were included if they reported on the prevalence or risk of violence while trafficked, or the prevalence or risk of physical, mental or sexual health outcomes among people who have been trafficked. Two reviewers independently screened papers for eligibility and appraised the quality of included studies. Results: Thirty-seven papers reporting on 31 studies were identified. The majority of studies were conducted in low and middle-income countries with women and girls trafficked into the sex industry. There is limited but emerging evidence on the health of trafficked men and the health consequences of trafficking into different forms of exploitation. Studies indicate that trafficked women, men and children experience high levels of violence and report significant levels of physical health symptoms, including headaches, stomach pain and back pain. Most commonly reported mental health problems include depression, anxiety and post-traumatic stress disorder. Although serological data on sexually transmitted infections are limited, women and girls trafficked for sexual exploitation self-report symptoms suggestive of a high prevalence of infections. Limitations of the review include methodological weaknesses of primary studies and some differences in definition and operationalisation of trafficking, which hinder comparability and generalisability of the results. Conclusions: There is increasing evidence human trafficking is associated with high prevalence and increased risk of violence and a range of physical and mental health problems. Although more studies have emerged in recent years reporting on the health of trafficked men and people trafficked for forms of exploitation other than in the sex industry, further research is needed in this area. Appropriate interventions and support services to address the multiple and serious medical needs, especially mental health, of trafficked people are urgently needed.